The Classical Tradition of „Parting with St. Petersburg” as Reflected in Non-Classical Poetry of the 21st Century - Liapina, Larisa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article presents a certain tradition in the Russian classical lyrical poetry, which originates in the motif of a lyrical subject’s taking his leave of St. Petersburg – and reflecting on this parting. The lyrical plots and the poetics of such poems have been subject to evolution in the course of the 19th and the 20th century and developed into a number of typical forms; in the 21st century these forms have been in interaction and various poets have been using them. The article brings the analysis of the lyrical cycle Parting with St. Petersburg by Fiodor Gorodov, an amateur poet publishing on the Internet. The cycle constitutes an interesting realization of the genre and successfully brings together all its main varieties.